USED WEBSITE MADRUSH ORGANIZATION WITH JOOMLA - Heri Rachman; Linda Wahyu Widanti (Jurnal Sistem Informasi, 2010)
Internet use in the current period is not new anymore. Almost the whole worldknows. The Internet is the culmination of information technology on computersused. The Internet can introduce things in a clear, such as introducing yourself,business, and others. This can be done with the place known as a website.Madrush organizations and youth environmental information center in theMadrasah street. Hope the website Organizations Madrush can facilitate gettinginformation about the desired Madrush Organization and coordination can bemore.